Effect of Social Media Marketing on The Conversion Rate of Deposit Money Banks in Nigeria - Enyioko, Newman C; Okwandu, Gabriel A (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2019)
The study examined the effect of social media marketing on the conversion rate of deposit money banks in Nigeria. Blog, Facebook, Twitter, and LinkedIn were used as the dimensions of social media marketing. The study revealed a gap from the literature that social media marketing and organizational efficiency of banks in Nigeria has not been extebsively studied in Nigeria. The study used the conversion rate as a dependent variable. The study adopted descriptive and inferential statistical tools to analyze the data and test the hypotheses. A questionnaire was used to elicit information from the respondents. The population of the study consisted of all the 22 banks approved by CBN. The study sampled 159 respondents from 22 banks in Nigeria and validly used 133 respondents representing 83.65% response rate for data analysis. The study found that banks use a blog, Facebook, Twitter, and LinkedIn to conduct their marketing activities for brand promotion and persuasion of customers to patronize them. The study revealed that Blog has a positive but insignificant effect on conversion rate.Â  The study discovered that Facebook has a positive and significant effect on conversion rate. The study revealed that Twitter has a positive and significant effect on conversion rate. The study found that LinkedIn has a positive and insignificant effect on conversion rate. The study concludes that as banks use blogs, Facebook, Twitter, and LinkedIn to create awareness about their products and services on the internet. The study recommends that bank managers should use Blog, Facebook, Twitter, and LinkedIn by encouraging all the bank staff to participate in social media marketing which in turn covers more ground for the enhancement of conversion rate leading to the conversion rate of banks.